2018
DOI: 10.3389/fmicb.2018.02990
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Bacterial Drug Efflux Pumps via Phyto-Therapeutics to Combat Threatening Antimicrobial Resistance

Abstract: Antibiotics, once considered the lifeline for treating bacterial infections, are under threat due to the emergence of threatening antimicrobial resistance (AMR). These drug-resistant microbes (or superbugs) are non-responsive to most of the commonly used antibiotics leaving us with few treatment options and escalating mortality-rates and treatment costs. The problem is further aggravated by the drying-pipeline of new and potent antibiotics effective particularly against the drug-resistant strains. Multidrug ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(90 citation statements)
references
References 181 publications
1
86
0
3
Order By: Relevance
“…For example, the super resistant bacterium Staphylococcus aureus can specifically degrade penicillin by producing β-lactamase, and on the other hand, it can deprive methicillin of its ability to bind cell wall mucin synthase by producing PBP2a protein [27]. In another super bacterium Pseudomonas aeruginosa, in addition to being able to produce different drug efflux pumps to resist multiple types of antibiotics [28,29], resistance genes can also be obtained through horizontal gene transfer [30,31], and its bacteria changes in body shape and dense biofilms can resist almost all antibiotics on the market [32,33]. In recent years, researchers have found that the formation of bacterial biofilm resistance to bacteria is particularly important.…”
Section: Microbial Resistance Mechanismsmentioning
confidence: 99%
“…For example, the super resistant bacterium Staphylococcus aureus can specifically degrade penicillin by producing β-lactamase, and on the other hand, it can deprive methicillin of its ability to bind cell wall mucin synthase by producing PBP2a protein [27]. In another super bacterium Pseudomonas aeruginosa, in addition to being able to produce different drug efflux pumps to resist multiple types of antibiotics [28,29], resistance genes can also be obtained through horizontal gene transfer [30,31], and its bacteria changes in body shape and dense biofilms can resist almost all antibiotics on the market [32,33]. In recent years, researchers have found that the formation of bacterial biofilm resistance to bacteria is particularly important.…”
Section: Microbial Resistance Mechanismsmentioning
confidence: 99%
“…This effect is mainly attributed to the inhibitory capacity of EPs of the phytochemicals present in the extract [ 172 ]. The activity of these plant molecules as inhibitors of microbial efflux pumps can act as restorers of antimicrobial susceptibility and open the door to combined antibiotic treatments, since these could exert their action more easily by not being expelled from the bacterial interior, allowing relive obsolete or discarded therapies due to this resistance mechanism [ 173 ]. A catechin, (-)-epigallocatechin gallate (EGCg), has shown sensitizing activity in S. aureus against tetracycline by inhibiting EPs such as Tet (K), increasing intracellular retention of the antibiotic and enhancing its effect [ 174 ].…”
Section: Resultsmentioning
confidence: 99%
“…In S. aureus, several multidrug efflux pumps, such as NorA, NorB and MepA, have been described that are associated with resistance to antibiotics, and NorA is the most important and well characterized efflux pump (Holler et al 2012;Astolfi et al, 2017;Felicetti et al, 2017;Felicetti et al, 2018). It is reported that the stable hydrogen bonding interactions between ginsenoside Rh2 (G-Rh2) and Gln51/Asn340/ Ser226 residues at active binding site in the central cavity of protein was responsible for the inhibition of NorA pump, thus G-Rh2 could be used as an inhibitor of the NorA efflux pump to restore susceptibility to common antibiotics in multiple drug resistant (MDR) bacteria (Zhang et al, 2014;Shriram et al, 2018;Kumar et al, 2020). Meanwhile, G-Rh2 is one of the active compounds extracted from ginseng, exhibiting unique immune enhancement effect different from other efflux pump inhibitors (Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%